Increasing Society's Knowledge about The Prevention of Respiratory, Hypertension, and Tb Pulmonary Diseases in Lihu Village, Railaco Administrative Post, Ermera Municipality, Timor-Leste, from August to October 2023. - Conceição, José Ximenes da Conceição; Oqui, Maximiano; Gomes, Lídia; de Jesus Vaz Cabral, Teresa; de Jesus Leite, Ana do Rosario; Boavida Tilman, Carlos; da Silva Belo, Ostelino (Bhinneka Tunggal Ika : Jurnal Pengabdian Kepada Masyarakat, 2024)
The problem that occurs in Lihu village in various places is that some houses do not have basic sanitation, there is no access to clean water, lack of awareness to dispose of waste properly, and inadequate waste management. A total of 262 children aged 0?6 (14.86% of the population) havevarious illnesses, with 39 diagnosed with medical conditions such as IRA (57.14%), diarrhea (25.71%), skin diseases (11.42%), epilepsy (2.85%), and asthma (2.85%). Out of the 413 young people (23.43% of the population), two have been diagnosed with medical illnesses rheumatoid arthritis (50%) and TB (50%). A significant number of people are at high risk of respiratory and cardiovascular diseases due to smoking (42.61%) and alcohol consumption (54.72%). A total of 90 elderly people aged above 60 represent 5.10% of the population, out of which 39 have been diagnosed with various illnesses, including DM (2.56%), RA (23.07%), hypertension (28.2%), IRA (5%), stroke (2%), gastritis (5%), TB (12.8%), liver disease (2%), asthma (15%), and skin disease (2%). Objective: The objective is to use community service to serve the community, through the resolution of their problems based on data obtained and promotion of their health. It is hoped that the community will understand and value their food chains, which play a principal role in the development of their bodies, and increase their knowledge to prevent illnesses. Through this community service, students can apply their academic skills to benefit the community. Method of community service: The implementation of the community health service activity uses an experimental method with a community trial approach. The implementation stage of the community health service activity started on August 25th until October 7th, 2023, in Liho village, Rai?lako subdistrict, Ermera municipality Timor?Leste. In the first stage of implementation, data was collected in the health center and entered the community to obtain information about the prevalent illnesses. Following this, the community was informed of the results and agreed to implement the program. Result: The result of the community service is an increase in the community's knowledge regarding the prevention of illnesses and most communities are satisfied with the implementation